Contextual Modulation of Physiological and Psychological Responses Triggered by Emotional Stimuli - Fujimura, Tomomi; Katahira, Kentaro; Okanoya, Kazuo (Frontiers in Psychology, 2013)
A series of emotional events successively occur in temporal context. The present study investigated how physiological and psychological responses are modulated by emotional context. Skin conductance response (SCR), heart rate, corrugator activity, zygomatic activity, and subjective feelings during emotional picture viewing were measured. To create an emotional context, a unpleasant or pleasant picture was preceded by three types of pictures, i.e., unpleasant, pleasant, and neutral pictures, resulting in six pairings. The results showed that viewing an unpleasant picture attenuated pleasant feelings induced by the following pleasant picture. On the other hand, preceding pleasant pictures decreased SCR to the following pictures. The effects of contextual modulation on emotional responses might be due to the informative function of pre-existing feelings; unpleasant feelings signal a threatening environment, whereas pleasant feelings signal a benign environment. With respect to facial muscle activities, viewing a pleasant picture decreased corrugator activity in response to the preceding picture. These findings suggest several types of contextual modulation effects on psychological, autonomic, and somatic responses to emotional stimuli.